Dalla sacralità alla qualità della vita: La bioetica cattolica nell’era della Covid-19 = From sanctity to quality of life : Catholic bioethics in the era of Covid-19 - Lo Sapio, Luca (Quaderni di diritto e politica ecclesiastica, 2021)
Covid-19 is a major challenge for transformation in human species. In particular, health and illness should be revised as far as we need to reshape our categories and strategies for action. The common and widespread use of categories such “catholic and secular Bioethicsµ or “Ethics of sanctity of life and Ethics of quality of lifeµ are partially inadequate to picture the current debate. New categories are on the plate: biorealism and biodenialism. Biorealism refers to the attitude of those who recognize the actual state of affairs of our planet and put their efforts to find a solution; biodenialism refers to those who reject the idea of an ultimate harm problem and try to defend the status quo of humanity as a whole. The idea that the traditional categories of Catholic Bioethics and Secular Bioethics are no longer available as the major instrument to understanding our reality implies that a new season of dialog is possible. Quality of life becomes a core issue for Catholic Bioethics whose aim is to reassess the interaction between humankind, non-human animals and environment.